Design, Synthesis, Anticonvulsant Activity, Preclinical Study and Pharmacokinetic Performance of N-[3-(4-chlorophenyl)-4-oxo-3, 4-dihydroquinazolin- 2-yl] methyl, 2-[(2-isopropyl-5-methyl) 1-cyclo Hexylidene] Hydrazinecarboxamide - Yadav, Meena K.; Tripathi, Laxmi (Central Nervous System Agents in Medicinal Chemistry, 2019)
Background: N-[3-(4-chlorophenyl)-4-oxo-3, 4-dihydroquinazolin-2-yl] methyl, 2-[(2- isopropyl-5-methyl) 1-cyclohexylidene] hydrazinecarboxamide QS11 was designed by computational study. It possessed essential pharmacophoric features for anticonvulsant activity and showed good docking with iGluRs (Kainate) glutamate receptor. Methods: QSAR and ADMET screening results suggested that QS11 would possess good potency for anticonvulsant activity. QS11 was synthesised and evaluated for its anticonvulsant activity and neurotoxicity. QS11 showed protection in strychnine, thiosemicarbazide, 4-aminopyridine and scPTZ induced seizure models and MES seizure model. QS11 showed higher ED50, TD50 and PI values as compared to the standard drugs in both MES and scPTZ screen. A high safety profile (HD50/ED50 values) was noted and hypnosis, analgesia, and anaesthesia were only observed at higher doses. No considerable increase or decrease in the concentration of liver enzymes was observed. Optimized QS11 was subjected to preclinical (in-vivo) studies and the pharmacokinetic performance of the sample was investigated. The result revealed that the pharmacokinetic performance of QS11 achieved maximum plasma concentrations (Cmax) of 0.315 ± 0.011 μg/mL at Tmax of 2.0 ± 0.13 h, area under the curve (AUC0-∞) value 4.591 ± 0.163 μg/ml x h, elimination half-life (T1/2) 6.28 ± 0.71 h and elimination rate constant was found 0.110 ± 0.013 h-1 . Results and Conclusion: Above evidences indicate that QS11 could serve as a lead for development of new antiepileptic drugs.
Keywords: pharmacokinetic performance